STUDYING OF THE INFORMATION EXCHANGE PROCESS IN OFFICE LOCAL NETWORKS BY USING MATHEMATICAL APPARATUS OF THE QUEUING THEORY - Makogon, Helen; Musaiev, Ruslan; Dychko, Aleksandr; Krylenko, Ivan; Dumych, Yehor (Сучасні інформаційні системи, 2019)
The subject matter of the article is the process of information exchange in the office local networks of institutions on computers with different technical parameters. The goal of the study is to analyze client-server interaction with socket development of an effective and secure communication program іn the local network. The tasks to be solved are: to analyze the client-server interaction in the local network by using sockets, to create a code of communication in the local network for computers with different technical parameters using the mathematical apparatus of the queuing theory, to conduct research of the information exchange process in the system “client-server” in order to increase its effectiveness. General scientific and special methods of scientific knowledge are used. The following results are obtained. Today, the computer park used in the armed forces has a very large dispersion of technical parameters and installed software. Therefore, the organization of office local networks requires solving the scientific and technical task of implementing such an architecture that simultaneously meets the requirements of quality, speed, convenience and level of security of information exchange between computers with different Hardware and Software. It is expedient to use sockets for communication protocols allows simultaneous processing requests from a large number of users. At the same time, the administrator can adjust the settings at any time and redistribute ports on the servers. The use of the mathematical apparatus of the queuing theory enabled to conduct research of the information exchange process of the system "client-server" in order to increase its efficiency. Each server was described as a closed single-channel queuing system (QS) with unlimited idle time. Conclusions. The authors consider the implementation of the “client – server” architecture on the office local network, the successful solution of which will allow an organizations to work optimally and without interruption. The authors developed communication programme on the local network on computers with different technical parameters and tested the code to detect errors. The use of mathematical apparatus of the queuing theory enables to solve the tasks of structural and parametric synthesis of the local network of the institution and to work out the method of detecting distributed attacks on the network at the initial stage.